A Review of Classical Motivation Theories: A Study Understanding the Value of Locus of Control in Higher Education - Kovach, Mary (Journal of Interdisciplinary Studies in Education, 2018)
This manuscript demonstrates the value of understanding locus of control in higher education.  Understanding this value provides educators with the ability to potentially predict academic outcomes, and have the foresight to guide students to achievement.  First, the manuscript identifies and explores the classic theories of motivation from the mid-1900s.  Then, a study is conducted that hypothesizes a correlation between demographic variables (age, gender, graduate/undergraduate classification) and locus of control using Rotter’s (1966) locus of control questionnaire.  Finally, examples from four different disciplines are provided.  This manuscript proposes suggestions for future research that will contribute to the findings of the overall construct of motivation, and more specifically, student locus of control in higher education.